Difficulties in Understanding the TOEFL Reading Test of English Language Education Study Program at University: DOI: 10.24256/ideas. v12i1.5179 - Usman, Nurhayati; Hendrik, Hendrik; Madehang, Madehang; Wisran (Institut Agama Islam Negeri Palopo, 2024)
This research aims to investigate the difficulties faced by students in understanding the TOEFL Reading test and to find the factors that influence the difficulties in understanding the TOEFL Reading test of English Language Education Study Program at IAIN Palopo. This research used descriptive qualitative method. The subjects of this research were 13 of the 3th semester in the English Department of IAIN Palopo in the 2023/2024 academic year. The instruments used to collect data were the TOEFL Reading test consisting of 50 questions in the form of multiple choice and an interview consisting of 5 questions. Based on the analysis of the TOEFL test results, it was found that the unstated detail question is the most difficult question faced by students and the question has been classified into the most difficult question based on the difficulty index formula. Meanwhile, the interview results show that students' opinions regarding the factors that influence the difficulty of understanding the TOEFL Reading test were lack of focus, time management, vocabulary mastery, lack of understanding of the aspects of the questions contained in the TOEFL questions, and lack of practice working on questions or taking the TOEFL test.